2012
DOI: 10.1523/jneurosci.5553-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissociation between Anterior and Posterior Temporal Cortical Regions during Retrieval of Remote Memory

Abstract: Retrieval of remote memory is considered to differentially involve the anterior and posterior temporal neocortices. Previous neuropsychological studies suggest that the different posterior temporal cortical regions are involved in the retrieval of remote memory of different categories of stimuli, whereas the anterior region is involved more generally in remote memory retrieval. In the present study, using functional magnetic resonance imaging of human brains, we tested this dissociation by examining the more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 77 publications
(119 reference statements)
0
20
0
Order By: Relevance
“…Consistent with the notion that hippocampal representations maintain episodic specificity, recent imaging studies have shown that multivariate representations of specific memories are reinstated in the hippocampus during successful remembering (Tompary et al, 2016; Mack and Preston, 2016). With respect to univariate activation, some work highlights that hippocampal activation during retrieval decreases with the age of the memory (Takashima et al, 2006, 2009; Watanabe et al, 2012). At the same time, other work demonstrates that hippocampal activation is related to remote retrieval for memories that retain distinct episodic elements (Viard et al, 2007; Harand et al, 2012; Sterpenich et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the notion that hippocampal representations maintain episodic specificity, recent imaging studies have shown that multivariate representations of specific memories are reinstated in the hippocampus during successful remembering (Tompary et al, 2016; Mack and Preston, 2016). With respect to univariate activation, some work highlights that hippocampal activation during retrieval decreases with the age of the memory (Takashima et al, 2006, 2009; Watanabe et al, 2012). At the same time, other work demonstrates that hippocampal activation is related to remote retrieval for memories that retain distinct episodic elements (Viard et al, 2007; Harand et al, 2012; Sterpenich et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggesting that these systems may contribute independently to cross-modal associations is consistent with this proposal. Neurophysiological and neuropsychological studies suggest that the knowledge-based processes involved in semantic memory and the more information-driven processes involved in multisensory integration may have independent but complementary roles in the formation of an object concept (Watanabe et al, 2012). In particular, the perirhinal cortex in the anterior temporal lobe is reported to be involved in the formation of meaningful, semantic object concepts whereas the posterior ͳ superior temporal sulcus (pSTS) is involved in the integration of pre-semantic object features across modalities (Beauchamp, Lee, Argall and Martin, 2004;Taylor, Moss, Stamatakis and Tyler, 2006).…”
Section: Semantic Memory and Top-down Influencesmentioning
confidence: 99%
“…Regardless, by choosing seeds based on activity, these procedures are affected by the limitations of activity-based methods highlighted above and would fail to identify region X (since its activity is not category selective). Some studies have attempted to consider functional connectivity more broadly by using MVPA to classify patterns of correlations amongst multiple regions both at rest (e.g., Dosenbach et al, 2010) and during tasks (e.g., Pantazatos et al, 2012; Watanabe et al, 2012; Mokhtari & Hossein-Zadeh, 2013). However, in these studies, only a small number of regions were selected relative to the total number of voxels in the brain, and this selection was based on activity in the same or other studies, or on coarse anatomical parcellations of the brain.…”
Section: Introductionmentioning
confidence: 99%